New approaches in the management of spasticity in multiple sclerosis patients: role of cannabinoids - Paul F Smith (Dove Medical Press, 2010)
Paul F SmithDepartment of Pharmacology and Toxicology, School of Medical Sciences, University of Otago, Dunedin, New ZealandAbstract: Cannabinoids such as Cannabis-based medicinal extracts (CBMEs) are increasingly being used in the treatment of spasticity associated with multiple sclerosis (MS). They have been shown to have a beneficial effect on spasticity; however, this evidence is largely based on subjective rating scales. Objective measurements using the Ashworth scale have tended to show no significant effect; however, the validity of this scale has been questioned. The available clinical trial data suggest that the adverse side effects associated with using CBMEs are generally mild, such as dry mouth, dizziness, somnolence, nausea and intoxication. However, most of these trials were run over a period of months and it is possible that other adverse side effects could develop with long-term use. There may be reason to be concerned about the use of therapeutic cannabinoids by adolescents, people predisposed to psychosis and pregnant women.Keywords: multiple sclerosis, spasticity, cannabinoids, Cannabis